Optical, Physical and Structural Properties of Er3+ Doped Low‐Phonon Energy Vitreous Matrix: ZnO‐B2O3‐TeO2. Issue 13 (8th May 2018) - Chopra, Neetu; Kaur, Sandeep; Kaur, Manpreet; Singla, Shivani; Marwaha, Ritika; Sharma, Gopi; Heer, Manmohan Singh
Abstract : This paper reports on the effect of varying concentration of erbium (Er 3+ ) on the (70‐ x /2) TeO2 − (20‐ x /2) B2 O3 −10 ZnO − x Er2 O3 (where x  = 0, 0.5, 1.0, 2.0, 2.5 mol.%) system, fabricated using the conventional melt quenching technique. The impact of Er 3+ on the structural, physical, and optical properties of these zinc borotellurite glasses is investigated using Fourier transform infrared spectroscopy (FTIR), density measurements and UV–vis spectroscopy. The amorphous nature is confirmed using X‐Ray diffraction. FTIR results reveal that the glass is formed of fundamental borate and tellurite network units. The addition of Er2 O3 results in the formation of TeO3 at the expense of Te‐O‐Te linkage. The UV–vis spectroscopy results show that Er 3+ enter the glass matrix showing absorption peaks corresponding to 4f‐4f transitions of trivalent Erbium ions (Er 3+ ) from ground state 4 I15/2 to the excited states 4 F5/2, 4 F7/2, 2 H11/2, 4 S3/2, 4 F9/2, 4 I9/2, 4 I11/2, and 4 I13/2 . The optical band gap tends to decrease and refractive index increases with the increase in Er 3+ concentration hence making these materials more efficient for the optical devices such as light emitting devices and image sensors. Abstract : This paper reports on the effect of varying concentration of erbium (Er 3+ ) on the (70‐ x /2) TeO2 ‐ (20‐ x /2) B2 O3 ‐10 ZnO ‐ x Er2 O3 (where x  = 0, 0.5, 1.0, 2.0, 2.5 mol.%) system, fabricated using the conventional melt quenching technique. The impact of Er 3+ on the structural, physical, and optical properties of these zinc borotellurite glasses is investigated. The amorphous nature is confirmed using X‐ray diffraction.